2017
DOI: 10.1021/acs.joc.6b02737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electron Spin Relaxation of Tetracarboxylate Pyrroline Nitroxides

Abstract: We report the design, synthesis, and electron spin relaxation properties of hydrophilic tetracarboxylate ester pyrroline nitroxides 1 and 2, which serve as models in the search for new spin labels for DEER distance measurement at room temperature. The nitroxides are designed to have the methyl groups further away from the N–O spin site to decrease the inequivalent couplings of the unpaired electron to the methyl protons that shorten Tm at T > 70 K in currently used labels. The key step in the synthesis of 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
2
29
0
1
Order By: Relevance
“…The Hamiltonian parameters obtained by simulation of the spectra are in Table 2, along with the values reported previously for 1 and 2 in 9:1 trehalose:sucrose [5]. These g values are similar to those for a wide range of nitroxides [8, 23, 24, 25].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The Hamiltonian parameters obtained by simulation of the spectra are in Table 2, along with the values reported previously for 1 and 2 in 9:1 trehalose:sucrose [5]. These g values are similar to those for a wide range of nitroxides [8, 23, 24, 25].…”
Section: Resultssupporting
confidence: 71%
“…The preparation of 9:1 trehalose:sucrose glasses was performed as reported previously [5] with a 2000:1 molar ratio of sugars to 3 . The addition of sucrose to the trehalose enhances glass formation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since deuteron has a ca. 6.5 times smaller gyromagnetic ratio than the proton, replacement of CH 3 groups by CD 3 groups should significantly suppress the magnetic relaxation induced by rotations of these groups [ 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that, when immobilized in trehalose/sucrose glass, these nitroxides possessed relatively long electron spin phase memory times ( T m ) and short spin–lattice relaxation times ( T 1 ) at room temperature [18]. Therefore, spin labels derived from 4 and 5 should provide highly promising tools for determination of distances by DEER (or DQC) in doubly labelled biomolecules at room temperature [19-21]. …”
Section: Introductionmentioning
confidence: 99%